Isolation of Sillica from Pantai Cermin Sand and Modification with Sodium Lauryl Sulfate and Ligan Ethylendyamine Through Coating Method as Absorption of Pb Metal - Saur Lumban Raja; Simon Putra Lubis (Journal of Chemical Natural Resources, 2023)
Research on the formation of synthesis and modification coating of silica and obtained silica with a quartz structure used to absorb lead metal ions. This isolation was performed by extracting silica from sand with the co-precipitation method using NaOH 7M and then adding HCl 2M. The resulting silica was coated with sodium lauryl sulfate and ethylenediamine to increase adsorption. The FT-IR spectrum on silica shows the presence of Si-O-Si, Si-O-, Si-OH, S“O, SO3, CH2, and NH”Sillica coating, which sodium lauryl sulfate and ethylenediamine ligands were carried out by coating method at pH 2. The results obtained before and after coating on silica were characterized by FT-IR, XRD, and SEM EDX analysis. The FT-IR spectrum on sillica showed the presence of Si-O-Si, Si-O, and Si-OH functional groups. After the coating, there was a change in the spectrum, indicating new functional groups in the S-O, SO3, CH2, and NH spectra. Characterization using XRD shows the diffraction peaks were of 2ð›³ 27,6297°, which indicates the amorph. After coating, the diffraction peaks appeared at an angle of 2ð›³ in the area of 19.62 °, 20.47°, 21.04 °, 25.56 °, 26.50 °, and 29.73 ° with a high enough intensity indicating increased crystallinity. The morphology, composition, and size of the silica produced before and after coating were observed by SEM-EDX. Where there is a change in the size before and after a modification, that is 100,788 nm to 85,3773 nm. Silica before and after coating is used as an adsorbent to reduce levels of heavy metal lead (Pb). This analysis showed that the adsorption of PbÂ²âº with silica was 4,5162 ppm, while the adsorption of PbÂ²âº after coating was 1,1146 ppm.